Reconstructing Landscape to Reconstruct Regionalism? L'Horta, la Ciutat de les Ciències, and the Ideological Politics of Valencian Modernity - Prytherch, David L. (Treballs de la Societat Catalana de Geografia, 2008)
In this paper I explore the ways economic and political reterritorialization such as regionalist politics in Spain may be negotiated through cultural discoursesand landscapes. Few regions exemplify the contradictions of regional politicsbetter than the Comunitat Valenciana, whose capital Valencia has been transformedby the Generalitat Valencianas simultaneous pursuit of economic developmentand political autonomy over two decades and three political administrations.Some of these changes imply the displacement of LHorta de Valencia, longa regional symbol, by new monumental spaces like the Ciutat de les Arts i de lesCiències. I examine this precipitous substitution of landscapes, in regional spaceand iconography, to analyze how the Generalitats reconstruction of the Valencianlandscape may serve to reconstruct Valencian regionalism. In this essay, based ona broader qualitative research project, I suggest that a new regionalist discoursehas emerged premised on global competitiveness and obsessed with modernity.Like the Museu de les Ciències itself, however, this new Valencian regionalismmay be built for global tourism yet lacking substantial content.